2011
DOI: 10.1109/tvcg.2011.189
|View full text |Cite
|
Sign up to set email alerts
|

Distance Visualization for Interactive 3D Implant Planning

Abstract: Fig. 1. Distance visualization for interactive (> 30 fps) preoperative implant planning using color coding on the implant surface (left), oriented distance glyphs (middle), and color coding on the implant surface and on a set of additional axial slices (right).Abstract-An instant and quantitative assessment of spatial distances between two objects plays an important role in interactive applications such as virtual model assembly, medical operation planning, or computational steering. While some research has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Thus, we do not highlight this group as a category in our result table. The two studies we found ( [32] and [33]) are, however, discussed throughout the paper.…”
Section: Glyph Types and Data Encodingmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, we do not highlight this group as a category in our result table. The two studies we found ( [32] and [33]) are, however, discussed throughout the paper.…”
Section: Glyph Types and Data Encodingmentioning
confidence: 90%
“…Patients rated by psychiatrists [21] Minnesota Multiphasic Personality Inventory Medical data [32] unknown Medical images [56] unknown Cars dataset [34] http://davis.wpi.edu/ xmdv/datasets/cars.html Project plans [35] unknown MM5 weather information [36] unknown Weather information [37] NCEP forecast model Weather information [42] Operational Regional Atmospheric Prediction System Modified U.S. census data [38] unknown Financial data [40] Investment in education USA (2008) Financial data [84] Wall Street Journal Index (1974 and 1975) Financial data [85] Standard and Poor's firm list (1974 and 1975) Classical music data [41] unknown k data [43] Lostpedia wiki edits Network data [44] 10 best ranked movies (IMDb) Google search results [45] http://www.google.de Marathon runners [50] unknown Power plant statistics [53] unknown Audio information [62] One laptop per child sound library Biological data [70] unknown Economic variables [77] U.S. Department of commerce & labor Tensor data [92] DTI dataset possible confounding factors, so as to better reason about changes in performance when modifying specific aspects of the same design [91], or when comparing it with other representations [48], [49], [50], [54], [64], or layouts [55].…”
Section: Dataset Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the medical field, some clearance visualization methods are known to assist in the navigation of implants in virtual environments [17,18]. These methods are too specialized for simply visualizing the clearance distance around objects.…”
Section: Thickness/clearance Definitions and Analysismentioning
confidence: 99%
“…They do not discriminate between two results which are badly segmented in different regions (e.g., top and bottom of an organ). Visual inspection concerns individual instances shown in 2D and 3D views such as ITK Snap (www.itksnap.org) or overlay the two meshes using transparency, color-coded local distances between vertices, e.g., [6,2,5,13]. These views are very detailed, but require manual inspection of all instances individually.…”
Section: Related Workmentioning
confidence: 99%